The Location Determination, Personal Selling and Price Perception on Consumer Purchase Decisions of Housing Development Companies in Eastern Bekasi - Anwar, Misbahul; Andrian, Andrian; Yoganingsih, Tutiek; Navanti, Dovina (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to investigate how customers' opinions of pricing, personal selling, and location affect their decisions to buy from Eastern Bekasi housing development companies. The nature of this kind of research is quantitative. This study had fifty participants. using the saturation sampling technique. Fifty respondents made up the study's sample size. Using Google Forms to distribute questionnaires is one method of gathering data. In this work, The hypotheses were evaluated using multiple linear regression analysis. Customers who have purchased and occupied housing units from Eastern Bekasi's dwelling development companies make up the research participants. The research's conclusions demonstrate that the elements of pricing perception, personal selling, and location all considerably and favorably affect the purchase decision variable.